2017
DOI: 10.22456/1679-9216.80212
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Bovine Adenovirus and Enterovirus Antibodies Reveals Different Infection Dynamics in Cattle Herds

Abstract: Background: Bovine enterovirus (BEV) and bovine adenovirus (BAV) are widely distributed in cattle population, and are among possible causes of gastroenteritis and respiratory disease, respectively, although the infection is more often subclinical. BAV infection may be also related to conjunctivitis, and may lead to severe infections and death in immunosuppressive calves. BEV infections have been associated with disorders of respiratory and reproductive tracts, and diarrhea. There is little available informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…In the first stage of our study, we confirmed the presence of antibodies (titres from 1 : 20 to 1 : 160) against BEV-E in nine out of ten cows the blood of which was used as our research material. This finding is fully consistent with results reported by other authors ( 2 , 11 ). For example, in their study conducted in Turkey, Birdane and Gür ( 2 ) determined the presence of specific antibodies against EV-E in 153 out of 155 clinically healthy dams (98.7%), and the titres ranged from 1 : 5 to 1 : 160.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the first stage of our study, we confirmed the presence of antibodies (titres from 1 : 20 to 1 : 160) against BEV-E in nine out of ten cows the blood of which was used as our research material. This finding is fully consistent with results reported by other authors ( 2 , 11 ). For example, in their study conducted in Turkey, Birdane and Gür ( 2 ) determined the presence of specific antibodies against EV-E in 153 out of 155 clinically healthy dams (98.7%), and the titres ranged from 1 : 5 to 1 : 160.…”
Section: Discussionsupporting
confidence: 94%
“…For example, in their study conducted in Turkey, Birdane and Gür ( 2 ) determined the presence of specific antibodies against EV-E in 153 out of 155 clinically healthy dams (98.7%), and the titres ranged from 1 : 5 to 1 : 160. In another study conducted in Brazil, neutralising antibodies against BEV were detected in 411 out of 414 tested cattle of both sexes (99.2%), and the titres varied from 1 : 5 to >1 : 640 ( 11 ).…”
Section: Discussionmentioning
confidence: 95%
“…There are also studies in different countries on the seroprevalence of BEV. Gras et al (2017) performed a neutralization test on 415 serum samples from cattle in Brazil and found that 411 samples (99.2%) had neutralizing antibodies to BEV. This study also found that 91 (22.1%) of the BEV seropositive samples had a high neutralizing antibody titer (1/320).…”
Section: Discussionmentioning
confidence: 99%
“…Infected cattle can easily spread BEV through their feces. Wild ruminants are thought to play a role in transmitting BEV to domestic cattle (Gras et al, 2017). In general, there are few studies on BEV in Türkiye.…”
Section: Disease Virus Equine Rhinitis a Virus) Cardiovirus (Cardiovi...mentioning
confidence: 99%